2009
DOI: 10.1007/s11832-009-0174-9
|View full text |Cite
|
Sign up to set email alerts
|

Early reduction versus skin traction in the orthopaedic treatment of femoral shaft fractures in children under 6 years old

Abstract: Background Femoral shaft fractures occur very frequently in children, and their prognosis usually is good. Nonoperative treatment is the gold standard for children under 6 years because of the excellent bony union and the remodelling qualities. Purpose The aim of this study was to compare two orthopaedic therapeutic methods: skin traction versus immediate reduction. Materials and methods The study involved 35 children, divided into two groups: in group 1, treatment consisted of skin traction for 21 days follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
(46 reference statements)
2
26
1
1
Order By: Relevance
“…[4,10,12,26,27] Seventy-seven percent of our study population were children of parents of low socio-economic status who could not afford operative management. It is therefore not surprising that the most common modality of treatment of paediatric femoral fractures in our setting was skin traction (87.7%) [ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,10,12,26,27] Seventy-seven percent of our study population were children of parents of low socio-economic status who could not afford operative management. It is therefore not surprising that the most common modality of treatment of paediatric femoral fractures in our setting was skin traction (87.7%) [ .…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] The choice of management is influenced by age and size of the patient, location and site of the fracture (fracture personality), associated injuries or multiple trauma, social circumstances or family issues and cost. [6][7][8] The treatment options include non-operative management with home traction, [9,10] immediate spica cast application [11,12] or a short period of traction followed by spica cast [13,14] and operative management with external fixation, [15][16][17] flexible intramedullary nailing [18,19] and plate fixation. [20,21] We treat paediatric femoral fractures with skin traction only or a short period of skin traction followed by plaster of paris hip spica cast in our centre.…”
Section: Introductionmentioning
confidence: 99%
“…The duration of cast immobilisation ranged from 4 -6 weeks and average time of union was 50 days. D'Ollonne T et al 6 in their study showed that cast immobilisation duration was 76.8 days in skin traction group and 61.5 days in early hip spica group. Angulation was within acceptable range in all cases except in 1 case, where 25 o of angulation was in sagittal plane.…”
Section: Discussionmentioning
confidence: 89%
“…Average duration of hospital stay was 1.5 days in our study. D'Ollonne T et al 6 found that mean hospitalisation was 18.8 days in skin traction group and 2.8 days in early hip spica group. The duration of cast immobilisation ranged from 4 -6 weeks and average time of union was 50 days.…”
Section: Discussionmentioning
confidence: 96%
“…4 After the age of 6 months and up to 5 years old, the standard treatment is a hip spica cast. [5][6][7] Some surgeons use skin or skeletal traction [8][9][10] or external fixators 11 either alone or in conjunction with hip spica casting. Over age 5, surgical treatments are more commonly used, including flexible titanium elastic nails, [11][12][13][14] submuscular bridge plates, 15,16 and eventually as the child gets closer to skeletal maturity, lateral entry intramedullary nails.…”
mentioning
confidence: 99%